1986
DOI: 10.1016/s0735-1097(86)80242-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic compromise (tricuspid stenosis and insufficiency) caused by an unruptured aneurysm of the sinus of Valsalva

Abstract: A patient is described with an unruptured aneurysm of the noncoronary sinus of Valsalva that occupied the right ventricular inflow tract and caused dynamic tricuspid stenosis and insufficiency. Results of two-dimensional echocardiography delineated the anatomy of the aneurysm and pulsed Doppler examination provided evidence that the aneurysm was unruptured. The unruptured aneurysm was resected successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…In our case, sinus of Valsalva aneurysm presented as a right atrial mass causing obstruction to tricuspid flow leading to right heart failure. Although, Gibbs et al 5 has reported a sinus of Valsalva with aneurysm causing right heart failure, but that was due to the presence of tricuspid stenosis, tricuspid regurgitation, but in contrast, our case had predominantly tricuspid stenosis with no tricuspid regurgitation leading to right heart failure.…”
Section: Discussion Of Managementcontrasting
confidence: 62%
“…In our case, sinus of Valsalva aneurysm presented as a right atrial mass causing obstruction to tricuspid flow leading to right heart failure. Although, Gibbs et al 5 has reported a sinus of Valsalva with aneurysm causing right heart failure, but that was due to the presence of tricuspid stenosis, tricuspid regurgitation, but in contrast, our case had predominantly tricuspid stenosis with no tricuspid regurgitation leading to right heart failure.…”
Section: Discussion Of Managementcontrasting
confidence: 62%
“…The most notable presenting feature of ruptured sinus aneurysm is congestive heart failure with a left to right shunt [5]. The most common clinical signs are dyspnea, pulmonary edema, with continuous murmur.…”
Section: Discussionmentioning
confidence: 99%
“…The unruptured aneurysms may go unnoticed for years, without any significant haemodynamic disturbance [1]. They may present with signs of right heart failure and a loud pulmonary flow murmur [2][3][4][5][6][7][8][9][10] or with a complete heart block caused by compression of the ventricular septum by the aneurysm [11,12]. Patients may rarely present with myocardial ischaemia, caused by coronary artery compression [10,13,14] or with dysphagia caused by oesophageal compression [15].…”
Section: Discussionmentioning
confidence: 99%